Canadian Jewish Barometer 2026: Pressures on Canadian Jews and their Responses - Brym, Robert; Lenton, Rhonda (Canadian Jewish Studies / Études juives canadiennes)

(untitled) (Association for Canadian Jewish Studies / Association d’études juives canadiennes, 2026)
This report is based mainly on a survey of 3,062 adult Canadian residents, including oversamples of Quebecers, Muslims, and Jews. The survey was in the field from January 15 to February 11, 2026. It focuses on how the attitudes of non-Jews toward Jews and Israel have changed since early 2024 and how that change has affected Canada’s Jews. Its main findings are as follows: (1) Non-Jewish Canadians’ attitudes toward Jews and especially toward Israel have become significantly more negative since 2024, (2) The percentage of individuals with negative perceptions of Jews and Israel varies in explicable ways across different groups and population categories, (3) In 2026 as in 2024, the correlation between attitudes toward Jews and attitudes toward Israel is moderate, so attitudes toward Israel are still important to understanding the spread of antisemitism, (4) Canadian Jews are most inclined to believe that attitudes toward Jews and Israel have grown more negative because of media coverage criticizing Israel’s actions during the war in Gaza and the way Israel actually prosecuted the war, (5) Canadian Jews are considerably more fearful of their position in Canadian society than they were in 2024 and believe that the situation will grow worse in the near future, (6) A rift has grown between Jews who believe the government of Israel should not be criticized insofar as it lacks viable strategic alternatives and Jews who believe the government of Israel should be criticized for adopting strategies that prevent compromise with the Palestinians and violate traditional liberal-democratic principles on which the Jewish state was founded. Based on these findings, the report recommends strategies for mitigating negative sentiment toward Jews and Israel and reducing polarization in the Jewish community.